Kajian Pustaka: Kontribusi Psychological Capital (Psycap) terhadap Program Pendidikan Kewirausahaan pada Pelajar Pancasila - Suparni, Novia Kusumaningsih; Alifka Alya Zhafirah; Nur Satriani; Sirajuddin Saleh (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to find out how psychological capital contributes to entrepreneurship education programs for Pancasila students. This research uses library research, reference materials using books, journals, articles by examining research publications taken from Google Scholar. The results of this research state that the context of psychological capital plays an important role in entrepreneurship education. The relationship between psychological capital and entrepreneurship education is becoming increasingly relevant considering the very complex changes in the business world today. A dynamic and uncertain business environment requires entrepreneurs who are not only skilled but also have strong mental and emotional strength. By integrating PsyCap in entrepreneurship education, this educational program can be more effective in preparing someone to become a successful and sustainable entrepreneur